Key Technology for Mechanical and Structural Design of Rectangular Curve Bottom Curtain Method for Salvage of “Yangtze River Estuary II” - ZHUANG Qianwei, YUAN Weihao, ZHANG Chi, YUAN Yixiang, LI Yanlong, ZHOU Dongrong (Shanghai Jiaotong Daxue xuebao, 2023)
The salvage of “Yangtze River Estuary II” ancient wreck adopted the world’s first curved pipe basing method. There existed various challenges in the mechanical and structural design. To satisfy the demands of non-contacting and subtle disturbance, this paper elucidates the configuration of the outer frame, the mechanical design of the pipe-jacking machine with a cutterhead of tribble planetary-gear cutters, and the structure design of the closely-assembled curved beam with high water-tightness. The practical application demonstrates that the developed pipe-jacking machine has subtle disturbance to the ancient wreck, and the water-tightness between the closely-assembled planetary-gear cutters is good, both of which effectively guarantee the originality and integrity of “Yangtze River Estuary II” ancient wreck and the cultural relics it carried on.